Living Faithfully according to James 1:2-8 - Manullang, Juanda; Lumy, Aghi (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Every believer has experienced temptation and has their own story in today’s world, which is increasingly practical and instantaneous. When faced with trials in life that cannot be resolved instantly, today’s believers ultimately decide to give up on the situation. As a result, faith is forgotten, and this is a problem in Christianity today. For this reason, this article examines the importance of living diligently in faith, as James advised believers who suffered from Roman colonialism. Using a qualitative approach and literature sources, this study will explore the importance of living with faith through fragments of the text of James 1:2-8. The main conclusion obtained is the need for a change in perspective among Christians regarding trials which must be seen as a process of strengthening faith and a way to practice perseverance. Only in that way will every trial faced be seen as a process fostering strong dependence and trust in God.